Platelet Count and Platelet Index as Prognosis Markers in Adult Septic Patients - Steven Tiro; Raehana Samad; Uleng Bahrun (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Sepsis is a major health problem with recent increase of incidence. One of life-threatening complications of sepsis is Disseminated Intravascular Coagulation (DIC). DIC in sepsis can trigger an increase of platelet destruction which can be assessed by platelet count and platelet index. Hence, this research aimed to analyze the correlation of platelet count and platelet index to the prognosis of adult septic patients. This research was then performed with a retrospective longitudinal study design. This research used the medical record data of adult septic patients at the Dr. Wahidin Sudirohusodo GeneralHospital in Makassar. The data of platelet count and platelet index were collected from routine blood of the patients for the first time they were diagnosed with sepsis. In total, this research was performed on 100 adult sepstic patients. Fifty of those patients had a good prognosis (cured), while the other fifty patients had a poor prognosis (died). Statistical results showed that the platelet count in the adult sepsis patients with a poor prognosis was significantly lower than those in patients with a good prognosis with median/minimum-maximum of 157,000/12,000-626,000 and 329,000/96,000-801,000, respectively (p=0.00). It was also known that there was no significant difference of MPV values between patients with poor prognosis and patients with good prognosis with Mean±SD of 9.54±1.44 and 10.08±2.09, respectively (p=0.138). Unlike MPV values, PDW values in patients with poor prognosis were significantly higher than those in patients with good prognosis with Mean±SD of 16.7±6.26 and 11.25±2.13, respectively (p=0.00). Thus, it can be concluded that there was an inverse correlation between platelet count and PDW value (r = -0.58). PDW value, as a result, could be used as a prognosis marker for adult septic patients. However, it was recommended to perform further research as a prospective study by removing the possibility of bias.